Climate-smart development: adding up the benefits of actions that help build prosperity, end poverty and combat climate change - ClimateWorks Foundation, San Francisco; Akbar, Sameer; Kleiman, Gary; Menon, Surabi; Segafredo, Laura (Washington, DC, 2014)
"This report describes efforts by the ClimateWorks Foundation and the World Bank to quantify the multiple economic, social, and environmental benefits associated with policies and projects to reduce emissions in select sectors and regions. The report has three objectives: 1) to develop a holistic, adaptable framework to capture and measure the multiple benefits of reducing emissions of several pollutants; 2) to demonstrate how local and national policymakers, members of the international development community, and others can use this framework to design and analyze policies and projects; and 3) to contribute a compelling rationale for effectively combining climate action with sustainable development and green growth worldwide. By using a systems approach to analyze policies and projects, this work illustrates ways to capitalize on synergies between efforts to reduce emissions and spur development, minimize costs, and maximize societal benefits. This report uses several case studies to demonstrate how to apply the analytical framework. Three simulated case studies analyzed the effects of key sector policies to determine the benefits realized in the United States, China, the European Union, India, Mexico, and Brazil. The sector policies include regulations, taxes, and incentives to stimulate a shift to clean transport, improved industrial energy efficiency, and more energy efficient buildings and appliances. Also presented are results of four simulated case studies that analyzed several sub-national development projects, scaled up to the national level, to determine the additional benefits over the life of each project, generally 20 years. By applying the framework to analyze both types of interventions, this report demonstrates the efficacy of this approach for national and local policymakers, international finance organizations, and others. These case studies show that climate change mitigation and air quality protection can be integral to effective development efforts and can provide a net economic benefit. Quantifying the benefits of climate action can facilitate support from constituencies interested in public health and food and energy security; it can also advance the international discussion of effective ways to address climate change while pursuing green growth. In this report, the chapter 1 provides background information on the pollutants covered in this report and identifies opportunities to achieve both local socioeconomic and global climate objectives by reducing emissions. It also introduces new modeling tools that enable broader economic analysis of emissions-reduction programs. Chapter 2 explains how these tools can be combined to develop an effective framework to analyze policies and projects. Chapter 3 demonstrates the framework, using several policy- and project-based case studies to estimate the multiple benefits of emissions reductions from a regional or national level. Finally, Chapter 4 explores the challenges to operationalizing the framework and presents conclusions from the study."